Upaya Meningkatkan Hasil Belajar Siswa Dengan Project Based Learning Melalui Penugasan Membuat Vlog Materi Trigonometri - Ely Hendriani (Departement of Mathematics Education, 2019)
This study aims to analyze the efforts in improving student learning outcomes in class XI IPA of SMA Negeri 1 Cikarang Timur with a model of learning project base learning through the assignment of making vlogs (video blogging) of simple trigonometric equation material. The method used is classroom action research, in which the subject of this study consisted of 30 students with a total of 14 male students and 16 female students, where an increase in student learning outcomes was obtained by changing the value above the minimum completeness criteria (KKM) of 11 Students (36.67%) to 24 Students (80%).